Mekanisme Sosial dan Kebijakan Sosial Lansia: Perbedaan Desa Industri dan Desa Agraris - Ambar Teguh Sulistiyani (Magister Administrasi Publik, 1999)
The ageing society as a result of a longer life expectancy is an important phenomenon in the twentieth century. During the 1980s, the early of the first stage of long term development in Indonesia, the rate of life expectancy only reach the age of 43. It then increased sharply to 64 in the period of 1995-2000. In 1980s the number ofelderly people was 11,4 million and it is predicted that in 2000 it would upsurge to 22,2 - million. Consequently, the situation is also followed by the increasing elderly dependency ratio of Indonesian population from 10% to 13% within last 15 years. It appears, therefore, that this new trend would has important effect on the issues of demography, economy, social and public administration. This paper tries to reveal the problem of the ageing population in terms of public administration and social mechanism. Empirical study is conducted in Keboansikep as a typical industrial district, and Sriharjo as a typical rural- agricultural district. The objective of this study is to recognize the role of the family, social mechanism, nongovernmental institution and the government policy as the societal elements which have been contributing integratively in providing social security for the elderly. The theoretical basis for this kind social policy can be drawn from the concepts of equity, welfare and societal necessities. More importantly, however, there are some technical aspect of such social security which should be understood by the public decision makers.